2020
DOI: 10.3389/fpsyg.2020.561785
|View full text |Cite
|
Sign up to set email alerts
|

The AGE Effect on Protective Behaviors During the COVID-19 Outbreak: Sociodemographic, Perceptions and Psychological Accounts

Abstract: COVID-19 outbreak is a sudden and devastating global pandemic in which the control of the spread is highly dependent on individual reactions, until the development of a vaccine and adequate treatments. Considering that older adults are at high risk for COVID-related medical complications and mortality, the present study focuses on the age-related differences on the adoption of protective behaviors during the initial stages of this outbreak, while accounting for the role of sociodemographic, COVID-related, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
112
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(144 citation statements)
references
References 56 publications
(116 reference statements)
17
112
2
Order By: Relevance
“…This result is in line with other studies conducted during the epidemics that reported a decrease in risk perception in the oldest-old (Fielding et al, 2005;Pasion et al, 2020). A possible explanation for this phenomenon could lie in the decrease of the fear of death with the age increase; in other words, the oldest-old group may be less worried about contracting an illness, and, therefore, shows a lower risk perception (Bruine de Bruin, 2020;Pasion et al, 2020). A complementary explanation concerns the decline in the executive functions in aging (Giorgio et al, 2010), as they underlie risk perception and risk-taking (Capone et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is in line with other studies conducted during the epidemics that reported a decrease in risk perception in the oldest-old (Fielding et al, 2005;Pasion et al, 2020). A possible explanation for this phenomenon could lie in the decrease of the fear of death with the age increase; in other words, the oldest-old group may be less worried about contracting an illness, and, therefore, shows a lower risk perception (Bruine de Bruin, 2020;Pasion et al, 2020). A complementary explanation concerns the decline in the executive functions in aging (Giorgio et al, 2010), as they underlie risk perception and risk-taking (Capone et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Although we did not compare older adults with younger individuals, we found the oldest individuals, i.e., the oldest-old group, perceiving a lower risk of contracting COVID-19 compared to the youngest ones, i.e., youngest-and middle-old groups. This result is in line with other studies conducted during the epidemics that reported a decrease in risk perception in the oldest-old (Fielding et al, 2005;Pasion et al, 2020). A possible explanation for this phenomenon could lie in the decrease of the fear of death with the age increase; in other words, the oldest-old group may be less worried about contracting an illness, and, therefore, shows a lower risk perception (Bruine de Bruin, 2020;Pasion et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another determinant of protective behaviors is one’s perception of the risk of COVID-19 [ 24 , 25 , 26 , 27 ]. In an online survey of Chinese adolescents, results showed that perception of COVID-19 risk positively affected their understanding of and participation in social distancing behaviors [ 27 ].…”
Section: Introductionmentioning
confidence: 99%